2014
DOI: 10.1016/j.clinthera.2014.06.036
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Minimization Analysis of Lanthanum Carbonate Versus Sevelamer Hydrochloride in US Patients With End-stage Renal Disease

Abstract: This real-world assessment of comparative phosphate binder drug costs between SH and LC among US patients with ESRD indicates that average cost savings with LC use increased with increasing SH doses. Conversion to LC from SH ≥ 5600 mg/d reduced drug costs and tablet burden while maintaining serum phosphate levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Filiopoulos et al [31] compared sevelamer hydrochloride and LC in patients on hemodialysis and found a beneficial effect of switching from sevelamer hydrochloride to LC in terms of reducing metabolic acidosis and hyperkalemia. Moreover, several studies have shown that switching from sevelamer to LC could reduce drug costs and tablet burden while maintaining serum phosphate levels within the normal range [32, 33]. Unfortunately, there were not enough RCTs available to compare these parameters between the various phosphate binders individually.…”
Section: Discussionmentioning
confidence: 99%
“…Filiopoulos et al [31] compared sevelamer hydrochloride and LC in patients on hemodialysis and found a beneficial effect of switching from sevelamer hydrochloride to LC in terms of reducing metabolic acidosis and hyperkalemia. Moreover, several studies have shown that switching from sevelamer to LC could reduce drug costs and tablet burden while maintaining serum phosphate levels within the normal range [32, 33]. Unfortunately, there were not enough RCTs available to compare these parameters between the various phosphate binders individually.…”
Section: Discussionmentioning
confidence: 99%
“…For end-stage renal disease patients, higher doses over time are often required as the disease progresses. Therefore, dosage of sevelamer for these patients was set to be 2.4 g/day in the first year, 4.8 g/day in years 2–4, 7.2 g/day in years 5–7, and 9.6 g/day from year 8 onwards [ 15 ]. Due to the lack of data on changes in dosage over time for patients on calcium carbonate and because of its very low cost relative to sevelamer, we assumed a constant dose (2.95 g/day).…”
Section: Methodsmentioning
confidence: 99%
“…None of the trials on LC reported any effect on inflammation or inflammatory biomarkers. Although LC is cheaper and more compliant compared to sevelamer [127], our target is not just to control phosphorus level. Sevelamer compounds have got more comprehensive trials that showed significant impact on patient mortality during predialysis stages and in incident HD.…”
Section: Management Of Non-traditional Risk Factorsmentioning
confidence: 99%